P01.147 Recurrent glioblastoma or therapy-related changes: The diagnostic accuracy of O-(2-[18F]-fluoroethyl)-L-tyrosine PET imaging. (19th September 2018) - Bashir, A; Jacobsen, S; Urup, T; Broholm, H; Grunnet, K; Møller, S; Henriksen, O; Larsen, V; Skjøth-Rasmussen, J; Skovgaard Poulsen, H; Law, I
Abstract: Background: Discrimination between recurrent glioblastoma and therapy-related changes with conventional magnetic resonance imaging (MRI) is challenging. There is increasing evidence for the clinical value of positron emission tomography (PET) with O-(2-18F-fluoroethyl)-L-tyrosine (FET) in addition to MRI in cases of ambiguous findings in the setting of posttreatment care. The diagnostic accuracy, however, varies among the published studies and is influenced by the composition of the population with different glioma subtypes/grades, lack of histological confirmation, and differences in data processing. Herein, we evaluated the diagnostic accuracy of FET PET scans in glioblastoma patients. Material and Methods: One hundred thirty-seven consecutive patients who had undergone 150 FET PET were reviewed retrospectively. Inclusion criteria were 1) histologically-proven glioblastoma; 2) previous surgery followed by oncological treatment consisting of standard radiochemotherapy or - if at second recurrence - chemotherapy; 3) unexplained constant or increasing contrast-enhancing (CE) lesions on T1, or non-CE lesions on T2 FLAIR MRI later than 6 months after radiotherapy, where the differentiation between disease recurrence or therapy-related changes was uncertain; 4) FET PET for supplementary evaluation; 5) a histological evaluation following surgery less than 3 months after FET PET, or MRI follow-up. FET PET scans were performed as 20-minute static PET/CT acquisitions and evaluated co-registered to T1 post-contrast MRI with measurement of maximum and mean tumor-to-brain ratios (TBRmax, TBRmean ). Receiver operating characteristics (ROC) analysis was used to determine the optimal threshold of FET parameters. The prognostic influence of FET parameters on overall survival (OS) was investigated with the Cox proportional hazards model. Results: The median time interval from radiotherapy until the radiological progression was 13 months. One hundred twenty-six PET scans demonstrated FET uptake of varying intensity. Surgical interventions were performed following 88 PET scans, while 62 PET scans were evaluated by clinical or MRI follow-up, resulting in 131 glioblastoma recurrences and 19 therapy-related changes. ROC analysis yielded the thresholds of 2.0 for TBRmax and 1.8 for TBRmean for differentiation between recurrent disease and therapy-related changes with the best performance of TBRmax with a sensitivity of 96% and a specificity of 100% (p < 0.0001). Using this threshold, 145 of 150 PET scans of glioblastoma recurrence or therapy-related changes were accurately classified. Multivariate survival analysis showed that TBRmax > 2.0 predicted independently a shorter OS in patients, who did not undergo subsequent therapy following PET (p = 0.002). Conclusion: FET PET is a powerful noninvasive tool to distinguish recurrent glioblastoma from therapy-related changes.